Novel quota and tax regime design approach for green transition: A case study on Switzerland's aviation industry. (December 2022) - Keshavarzzadeh, Amir H.; Thut, Caspar; Andersen, Daniel; Lingsch, Levi; Patt, Anthony G.
Abstract: In the present study, a novel approach for calculating optimal quota and tax regimes is investigated. A meta-heuristic framework has been developed to find the optimal quota regime for the national or worldwide aviation industry. The minimization of ticket prices and CO2 emissions are considered to be objective functions. The results of the current study indicate that implementing optimized quotas is more effective than intensive tax regimes. To elaborate, much more important than the value of the carbon price is the shape (convexity or concavity) of the tax regime. The optimal tax regime shape is also obtained. Based on the optimal quota and tax regime, the concept of golden time and value is introduced. In the golden time window, investing in Sustainable Aviation Fuels (SAFs) will be the most cost-effective. Furthermore, the results demonstrate that neither the sole introduction of quotas nor the imposition of high carbon taxes are beneficial from an economic and decarbonization standpoint. Thus, an optimized quota regime should be employed. These quotas should be introduced as soon as possible, and their implementation should be combined with political efforts to introduce a carbon tax and policies supporting the development of an alternative jet fuel industry. Highlights: Proposing a novel framework/approach for designing tax or quota regimes based on metaheuristic techniques. Studying the effect of convexity or concavity of tax and quota regimes on decarbonization and costs. Obtaining the robust optimal shape for the tax regime. Obtaining the most optimum quota regime shape and figure. Introducing the concept of golden time and value.